A REVIEW OF EMPLOYEE PERFORMANCE: MINI-REVIEW APPROACH - Lestari, Eka; Riyanto, Setyo (Dinasti Publisher, 2021)
Employee Performance relate to work motivation that exists in a person becomes a frame of reference in realizing a behavior directed at personal goals. In conclusion, In improving the employee performace and also employee commitment, a good organization should look at the level of job satisfaction of employees. From 17 articles on this mini review, we can find fact that employee performace have psotive correlation with job satisfaction. Such as High-performance work system has a significant positive effection employee creativity and employee performance, and employee creativity also has a significant positive effect on employee performance. Also we can look from the employee themselves, employees who are able to learn the position and meaning of a brand through their well-informed manager are in a better position to develop their own performance and ability, and related to company, it will give them possibility to have strong relationship to a brand, as well as to provide exceptional service to customers